Perancangan Sistem Informasi Absensi Siswa Menggunakan QR Code Berbasis Web - Vitriani; Gunawan Ali; Wahyu Nur Rohman; Melly Novalia (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The attendance system in education field is generally done manually, including school attendance, where this is very inefficient because there are often errors during the recapitulation process of student attendance data. The aim of this study is to design a Student Attendance Information System Using a Web Based QR Code to provide convenience in managing student attendance data. The type of research was Research and Development (R&D) with a Waterfall development model consisting of several stages, which are: Needs Analysis, System Design, Implementation, Testing, and Maintenance. The resulting system tested by using Black box test and validated by a system expert with the result is "Excellent" category which is validated by using usability aspect analysis through a questionnaire and the result of calculating the converted value is "Very Good". It shows that the Student Attendance Information System by using this Web-Based QR Code can provide convenience in managing data efficiently and make the attendance process more practical